On the normativity of expressing the belief in a just world: empirical evidence - Alves, H. (2017)
There is a large body of evidence that the belief in a just world (BJW) affects people's behaviors and attitudes, either through secondary victimization of innocent victims or the promotion of helping behavior. In this article, we aim to address the normativity of the very expression of BJW. Results of two experimental studies show that the expression of a higher degree of BJW is more socially valued than that of a lower one. We argue that this pattern should not only be seen as deriving from intrapersonal motivation to see the world as a predictable place, but also as a norm which seems to be perceived as having both social utility and desirability.